2021
DOI: 10.1126/scitranslmed.abb0036
|View full text |Cite
|
Sign up to set email alerts
|

A heterozygous germline CD100 mutation in a family with primary sclerosing cholangitis

Abstract: Primary sclerosing cholangitis (PSC) is a chronic inflammatory liver disease without clear etiology or effective treatment. Genetic factors contribute to PSC pathogenesis, but so far, no causative mutation has been found. We performed whole-exome sequencing in a family with autosomal dominant inheritance of PSC and identified a heterozygous germline missense mutation in SEMA4D, encoding a K849T variant of CD100. The mutation was located in an evolutionarily conserved, unstructured cytosolic region of CD100 aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…A large number of PSC susceptibility genes have been identified. Whole‐exome sequencing in a family with autosomal dominant inheritance of PSC revealed a heterozygous germline missense mutation in Sema4D encoding a K849T variant 80 . This mutation was associated with impairment of T‐cell functions and INF‐γ secretion.…”
Section: Semaphorins In Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of PSC susceptibility genes have been identified. Whole‐exome sequencing in a family with autosomal dominant inheritance of PSC revealed a heterozygous germline missense mutation in Sema4D encoding a K849T variant 80 . This mutation was associated with impairment of T‐cell functions and INF‐γ secretion.…”
Section: Semaphorins In Pathogenesismentioning
confidence: 99%
“…Whole-exome sequencing analysis demonstrated the involvement of Sema4D in PSC. 80 PSC is a severe hepatobiliary disease characterized by inflammatory and fibrotic bile duct lesions, in which multiple genetic and environmental factors are implicated. 81 There are neither early diagnostic markers nor effective therapies for PSC.…”
Section: Sema4d In Primary Sclerosing Cholangitis (Psc)mentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, spatial transcriptome analyses of human PSC-affected livers found biliary infiltrating immune cells with reduced surface CD100 98 , the gain-of-function mutation of which was previously identified as a causal mutation of the familial subtype of PSC. 99 areas from parenchymal areas in fresh-frozen human liver tissues from patients with endstage liver disease. 100 The cell deconvolution analysis by CIBERSORTx 101 detected a significant enrichment of estimated hepatocytes, cholangiocytes, and cycling cells in parenchymal regions and mesenchymal, endothelial, monocyte, innate lymphoid cells, B cells, and T cells in fibrotic areas, consistent with histological assessment.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…91 A recent study on a family where 5 individuals suffered from PSC, identified a heterozygous missense mutation in SEMA4D (encoding Semaphorin-4D/CD100) in all 5 individuals, further linking T cells to PSC pathogenesis. 92 This mutation was related to T-cell functional defects on the transcriptional and functional level in murine models and patient samples, and replacement by wild-type T cells in mice carrying the same diseasecausing mutation as the sick family members attenuated cholangitis after DDC (3,5diethoxycarbonyl-1,4-dihydrocollidine) exposure. 92 Although the CD100-mutation was private to this family, it represents the first casual mutation leading to PSC.…”
Section: Adaptive Lymphocytesmentioning
confidence: 99%